2015
DOI: 10.1245/s10434-015-4878-4
|View full text |Cite
|
Sign up to set email alerts
|

Verification of WFA-Sialylated MUC1 as a Sensitive Biliary Biomarker for Human Biliary Tract Cancer

Abstract: Biliary WFA-sialylated MUC1 is a useful biomarker for the differentiation of biliary tract cancer. The sensitivity of WFA-sialylated MUC1 was clearly higher than that of biliary cytology. Further data collection is necessary to validate the clinical usefulness of this biomarker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…They stated that LacdiNAc in N -glycans significantly decreases during progression of human breast cancer [13,14]. In contrast, the enhanced expression of LacdiNAc has been shown to be associated with the progression of human prostate, ovarian, colon, and liver cancers [12,15,16,17]. Therefore, the quantification of LacdiNAc glycan carrying glycoproteins or tissue-specific expression of LacdiNAc glycan detected by the WFA has shown promise as cancer glycobiomarkers [17,18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They stated that LacdiNAc in N -glycans significantly decreases during progression of human breast cancer [13,14]. In contrast, the enhanced expression of LacdiNAc has been shown to be associated with the progression of human prostate, ovarian, colon, and liver cancers [12,15,16,17]. Therefore, the quantification of LacdiNAc glycan carrying glycoproteins or tissue-specific expression of LacdiNAc glycan detected by the WFA has shown promise as cancer glycobiomarkers [17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the enhanced expression of LacdiNAc has been shown to be associated with the progression of human prostate, ovarian, colon, and liver cancers [12,15,16,17]. Therefore, the quantification of LacdiNAc glycan carrying glycoproteins or tissue-specific expression of LacdiNAc glycan detected by the WFA has shown promise as cancer glycobiomarkers [17,18,19]. In particular, regarding PCa, there are only three papers about LacdiNAc distribution in prostate biopsy (Pbx) and RP specimens using WFA [15,16,20], and they did not report the relation between WFA-reactivity in tissues and PCa prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, its cross-reactive potential severely limits its use for cancer biomarker detection. WFA is currently considered the most prominent diagnostic lectin against cholangiocarcinoma when compared with other homologous lectins (26,35) and the most discriminatory against altered N-glycans on Mac2-binding protein, a secretory N-glycoprotein with elevated expression levels during viral hepatitis induced liver cirrhosis (36,37).…”
mentioning
confidence: 99%
“…In many cancer cells, malignancy is correlated with overexpression of sialic acids on the cell surface [22]. It has further been shown that secreted sialylated mucins can be detected in the bloodstream of cancer patients [23], and lectins are valuable diagnostic tools [2426]. Thus, sialic acid specific lectins are useful tools for the detection and characterization of sialylated glycoconjugates displayed on the surface of cancer cells and tissues [27, 28].…”
Section: Introductionmentioning
confidence: 99%